Organokines and liver enzymes in adolescent girls with polycystic ovary syndrome during randomized treatments - Garcia-Beltran, Cristina; Peyrou, Marion; Navarro-Gascon, Artur; López-Bermejo, Abel; de Zegher, Francis; Villarroya, Francesc; Ibáñez, Lourdes (Frontiers in Endocrinology, 2024)
Introduction: Polycystic ovary syndrome (PCOS) is often related to metabolic associated fatty liver disease (MAFLD). MAFLD has been associated with altered hepatic function and systemic dysmetabolism and with abnormal circulating levels of signaling molecules, so-called organokines.Here, we assessed the effects of two randomized treatments on a set of organokines in adolescent girls with PCOS and without obesity, and report the associations with circulating biomarkers of liver damage which were assessed longitudinally in the aforementioned studies as safety markers.Liver enzymes [aspartate aminotransferase (AST), alanine amino transferase (ALT) and gamma-glutamyl transferase (GGT)] were assessed as safety markers in previous randomized pilot studies comparing the effects of an oral contraceptive (OC) to those of a low-dose combination of spironolactone-pioglitazone-metformin (spiomet) for 1 yr. As a post-hoc endpoint, the organokines fibroblast growth factor-21 (FGF21), diazepam-binding protein-1 (DBI) and meteorinlike protein (METRNL), were assessed by ELISA after 6 months on OC (N=26) or spiomet (N= 28).Auxological, endocrine-metabolic, body composition (by DXA) and abdominal fat partitioning (by MRI) were also evaluated. Healthy age-matched adolescent girls (N=17) served as controls.Results: Circulating ALT and GGT levels raised during OC treatment and returned to baseline concentrations in the post-treatment phase; in contrast, spiomet treatment elicited no detectable changes in ALT and GGT concentrations. In relation to organokines after 6 mo on treatment, (1) FGF21 levels were significantly higher in PCOS adolescents than in control girls; (2) DBI levels were lower in OC-treated girls as compared to controls and spiomet-treated girls; (3) no differences were observed in METRNL concentrations between PCOS girls and controls. Serum ALT and GGT levels directly correlated with circulating METRNL levels only in OC-treated girls (R=0.449; P=0.036 and R=0.552; P=0.004, respectively).The on-treatment increase in ALT and GGT levels occurring only in OC-treated girls associates with circulating METRNL levels suggesting an enhanced METRNL synthesis as a reaction to the hepatic changes elicited by OC treatment.